Beyond order : 12 more rules for life - Peterson, Jordan B. (Penguin ; Portfolio, 2021)
"As a follow-up to 12 Rules for Life, the author provides twelve additional rules related to the overarching theme of how the dangers of too much security and control might be profitably avoided"--